2019
DOI: 10.15302/j-laf-20190206
|View full text |Cite
|
Sign up to set email alerts
|

Nine Questions Toward Influences of Emerging Science and Technology on Urban Environment Planning and Design

Abstract: There is no doubt that science and technology have progressed rapidly in the past decade and it is constantly challenging and refreshing people's understanding of urban environment, human life, and even human nature itself. Meanwhile, its impact on urban environment planning and design should not be ignored and needs to be addressed promptly. The concept of science and technology is self-renewing and has no universal or authoritative definition. In a narrow sense, new science and technology may cover any new m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…American landscape designer Benjamin Bloom and colleagues found that pleasant university landscaping significantly improved the psychological well-being of university students, particularly in terms of stabilizing their internal emotions, alleviating their anxiety symptoms, and enhancing their well-being [34]. Emotions are the feelings and experiences that individuals have after being stimulated by the objective material world, and can generally be divided into positive and negative emotions [35]. Based on the interpretation of Corina Bogdan et al's study [36][37][38][39][40][41][42], in the context of positive psychology, a scientific and reasonable setting and design of university campus landscapes can enable university students to obtain more suitable places for personal solitude and social interaction, enhance their belonging and reliance on campus, and support their psychological mechanisms to pursue well-being.…”
Section: Outdoor Activities and Campus Landscape Contribute To The We...mentioning
confidence: 99%
“…American landscape designer Benjamin Bloom and colleagues found that pleasant university landscaping significantly improved the psychological well-being of university students, particularly in terms of stabilizing their internal emotions, alleviating their anxiety symptoms, and enhancing their well-being [34]. Emotions are the feelings and experiences that individuals have after being stimulated by the objective material world, and can generally be divided into positive and negative emotions [35]. Based on the interpretation of Corina Bogdan et al's study [36][37][38][39][40][41][42], in the context of positive psychology, a scientific and reasonable setting and design of university campus landscapes can enable university students to obtain more suitable places for personal solitude and social interaction, enhance their belonging and reliance on campus, and support their psychological mechanisms to pursue well-being.…”
Section: Outdoor Activities and Campus Landscape Contribute To The We...mentioning
confidence: 99%
“…However, for most high-density cities, it is tough to calculate the "increase and decrease" in the park green space problem, especially for large park green spaces in the city center (e.g., city-level and regional-level comprehensive parks); the measures needed to be taken are extremely challenging. The increase in urban population and the expansion of gray land have gradually reduced the per capita area of existing green space, and the difficulty and cost of new construction are also increasing, although often only at the planning level [6]. Under such circumstances, the marginalization of large parks and green spaces has become a more common phenomenon, and the "miniaturization" and "fragmentation" of parks and green spaces in urban centers has been a gradual trend [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in urban population and the expansion of gray land have gradually reduced the per capita area of existing green space, and the difficulty and cost of new construction are also increasing, although often only at the planning level [6]. Under such circumstances, the marginalization of large parks and green spaces has become a more common phenomenon, and the "miniaturization" and "fragmentation" of parks and green spaces in urban centers has been a gradual trend [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The entropy algorithm of LUM may not be the best tool for determining the association between land use and physical activities [37]. Green spaces and landscapes also encourage physical and psychological health [38], expediting the recovery of patients [39].…”
Section: Introductionmentioning
confidence: 99%
“…The entropy algorithm of LUM may not be the best tool for determining the association between land use and physical activities [37]. Green spaces and landscapes also encourage physical and psychological health [38], expediting the recovery of patients [39]. This study follows the WHO's framework and selects land use, transport, green space, and urban design as the four components of the built environment.…”
Section: Introductionmentioning
confidence: 99%